Residual limb modelling for optimal shape and bandaging in transfemoral amputees - Sudesh Sivarasu; Bhaveen Lalla; Chibuike Mbanefo; Roopam Dey; Michael Awood (Results in Engineering)
Effective compression bandaging of transfemoral residual limbs is essential for managing postoperative swelling and achieving a conical limb shape appropriate for prosthetic fitting. However, conventional bandaging techniques often lack personalised adjustment based on the residual limb’s changing dimensions, potentially compromising pressure consistency and therapeutic outcomes. This study aimed to demonstrate the modelling and validation of residual limbs for optimal shape and bandaging in transfemoral amputees, by integrating patient‑specific circumferential measurements into custom-printed A4 templates and mobile-driven guidance. Six residual limb models (ACM, CM1–CM5) were developed with incrementally increasing circumferential dimensions. Predicted bandage lengths were calculated for each model using Python scripts, and pressure readings were obtained using a Force Sensitive Resistor circuit, with outputs converted to mmHg based on calibration values. Statistical analyses were conducted, including chi-square goodness of fit tests and one-sample t-tests, to assess the differences between observed and expected values. Results demonstrated that differences between observed and expected bandage lengths were not statistically significant across all models, with mean differences increasing proportionally with model size. Pressure readings for most models remained within 0.5 mmHg of the approximated ideal target of 20 mmHg, with only CM5 showing a statistically significant deviation (mean pressure: 18.2 mmHg, p = 0.01), suggesting potential limitations at higher limb volumes. In addition, a consistent trend of increased pressure during diagonal wrapping steps (steps 2 and 3) and lower pressure during lateral and final steps (steps 1 and 4) was observed. These findings confirm the validity of the prediction model for bandage length and support the technique's effectiveness in applying therapeutic compression for optimal shape. This study establishes a foundation for optimising residual limb bandaging practices and suggests that further testing with larger models and clinical trials could enhance personalised compression therapy for amputees.